Exile (The University of North Carolina Press, 2026)
This work is a collection of twenty-four fundamental essays on the many-sided topic of German exile literature during and after Hitler's Third Reich. Exile literature, which emerged in the 1980s as a special field of critical investigation within German Studies, embraced the diverse works of writers who were scattered from Hollywood to Moscow but were related by the common bond of exile from Germany. Leading American and European specialists in the field are contributors to the volume, which discusses the work of Thomas Mann, Bertolt Brecht, Hermann Broch and Karl Wolfskehl among others.